Transcriptome mining of hormonal and floral integrators in the leafless flowers of three cymbidium orchids - Ahmad, Sagheer; Yang, Kang; Chen, Guizhen; Huang, Jie; Hao, Yang; Tu, Song; Zhou, Yuzhen; Zhao, Kai; Chen, Jinliao; Shi, Xiaoling; Lan, Siren; Liu, Zhongjian; et al. (Frontiers in Plant Science, 2022)
Flowering is the most studied ornamental trait in orchids where long vegetative phase may span up to three years. Cymbidium orchids produce beautiful flowers with astonishing shapes and pleasant scent. However, an unusually long vegetative phase is a major drawback to their ornamental value. We observed that under certain culture conditions, three cymbidium species (Cymbidium ensifolium, C. goeringii and C. sinense) skipped vegetative growth phase and directly flowered within six months, that could be a breakthrough for future orchids with limited vegetative growth. Hormonal and floral regulators could be the key factors arresting vegetative phase. Therefore, transcriptomic analyses were performed for leafless flowers and normal vegetative leaves to ascertain differentially expressed genes (DEGs) related to hormones (auxin, cytokinin, gibberellin, abscisic acid and ethylene), floral integrators and MADS-box. A significant difference of cytokinin and floral regulators was observed among three species as compared to other hormones. The MADS-box genes were significantly expressed in the leafless flowers of C. sinense as compared to other species. The data mining thus, outsources the valuable information to direct future research on orchids at industrial levels.